Overview of the 7th International Congress "Engineering, Environment and Materials in Process Industry": Event Review - Vujadinović , Драган; Beribaka, Мирјана (HEMIJSKA INDUSTRIJA (Chemical Industry), 2021)
The 7th International Congress "Engineering, Environment and Materials in Process Industry" – EEM2021, was successfully held on the mount Jahorina, from March 17th to March 19th, 2021. The EEM2021 congress gathered eminent researchers and professionals from over 30 countries. A total of 228 papers were submitted, and the fields of greatest interest were chemical engineering and technology, food technology, biotechnology, materials, and environmental sciences. This years event was supported by two internationally renowned scientific publishers – Springer-Nature and Wiley, who were kind enough to offer their scientific journals for the research results to be presented, together with other renowned EEM2021 supporting publications – SN Applied Sciences, Journal of Food Processing and Preservation, Health, Food & Biotechnology, Hemijska industrija, and the Journal of Engineering & Processing Management. Due to the COVID-19 outbreak, we were forced to adapt to this new situation, and this was the first time in the history of the Faculty of Technology Zvornik, University of East Sarajevo, that the congress was organized as a hybrid event – both in person and on a digital platform. This mode of organization enabled participants from all over the world to attend plenary lectures and invited speakers presentations, as well as to participate in an online poster session. The International Congress "Engineering, Environment and Materials in Process Industry" once again proved to be an opportunity for members of the scholarly community to exchange the results of their work internationally and gain insight into the possibilities of applying their research results in practice, despite the ongoing challenges of the modern world. The Organizing Committee and members of Faculty of Technology Zvornik would like to thank all the researchers, delegates, reviewers, endorsers, co-organizers and sponsors for their contribution to EEM2021. We would also like to invite researchers to join us in our next congress, which we hope will be held under much more fortunate conditions, and members of the Organizing Committee will do their best to outdo themselves and make the following event even better in every manner.